Pengaruh Pengungkapan Pertanggung Jawaban Sosial dan Struktur Tata Kelola terhadap Reputasi Perusahaan - Fitriasari, Rizka; Astuti, Vina Sri; Karis, Reyhan Achmad (Manajemen & Bisnis Jurnal, 2025)
Abstract. The purpose of this study is to identify the effect of corporate social responsibility disclosure and corporate governance structure including the number of board of commissioner members, percentage of independent commissioners, number of board of commissioners meetings, number of board of directors meetings, number of audit committee meetings, the presence of nomination and remuneration committee on firm reputation in manufacturing companies in Indonesia. The samples are 50 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2021 which were taken using purposive sampling. The findings indicate a positive effect of corporate social responsibility disclosure on firm reputation. This study also proves the positive effect of the number of board of commissioner members and the number of board of directors meetings on firm reputation. However, this study failed to prove that the percentage of independent commissioners, the number of board of commissioners meetings, the number of audit committee meetings, and the presence of nomination and remuneration committee can affect firm reputation. The sample of this study is limited to manufacturing companies listed on the Indonesia Stock Exchange. Empirical studies that focus on the influence of corporate social responsibility disclosure and corporate governance structure on firm reputation in Indonesian context using control variables firm size and firm age, especially in manufacturing companies, are still rare